Analisis Efisiensi Pemasaran Kelapa Sawit Petani Swadaya di Desa Sidomulyo Kecamatan Air Kumbang Kabupaten Banyuasin - Shazkia Martha Yolanda; Lifianthi Lifianthi; Henny Malini (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Yolanda SM, Lifianthi L, Malini H. 2021. Analysis of marketing efficiency of palm oil farmer in Sidomulyo village, Kumbang Water district, Banyuasin regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimalke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 911-923. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). The objectives of this study were, 1) Knowing the marketing channels for independent smallholders of oil palm in Sidomulyo, Air Kumbang District, Banyuasin Regency, 2) Calculating marketing margins, farmer shares and marketing efficiency of oil palm Fresh Bauh (FFB) for independent smallholders in Sidomulyo, Air District. Kumbang, Banyuasin Regency. The location was determined deliberately. Data collection in this study was conducted in November. The data collected are primary data and secondary data. The data collection method uses the Snowball Sampling method. The research method used is a survey method. The results of the research that have been carried out can be concluded, 1) There are two marketing channels in Sidomulyo Village, Banyuasin District, namely channel 1 covering, farmers-merchant collectors-big traders-palm oil factories, and, 2 marketing channels covering, farmers-largescale- palm oil mill, 2) Marketing channel 1 has a marketing margin of 500 IDR/kg, farmer share of 64.2% and an efficiency figure of 17.85%, which means that it is efficient because the number shows less than 50 %, as well as marketing channel 2 with a marketing margin of 300 IDR/kg, farmer share 78.5% and efficiency value 10.71% indicate that marketing channel 2 is efficient, because the smaller the percentage of marketing efficiency, the more efficient the marketing channel. It can be concluded that marketing channel 2 is more efficient than marketing channel 1 which is the results in lower efficiency values because the total marketing costs are not high and the marketing channel 2 is shorter than marketing channel 1.